Strengths, Weaknesses, Opportunities and Threats (SWOT) Analysis of the Implementation of Public Health Policies on HTLV-1 in Brazil - Miranda, Angelica Espinosa; Rosadas, Carolina; Assone, Tatiane; Pereira, Gerson Fernando Mendes; Vallinoto, Antonio Carlos Rosário; Ishak, Ricardo (Frontiers in Medicine, 2022)
Human T lymphotropic virus 1 (HTLV-1) is a public health issue for most countries and imposes important consequences on patients' health and socioeconomic status. Brazil is one of the global leaders of the public health response to these viruses. The country has challenges to overcome to implement meaningful policies aiming to eliminate HTLV-1/2. An analysis of strengths, weaknesses, opportunities, and threats (SWOT) for the implementation of public health policies on HTLV-1/2 was performed. The strengths identified were the Brazilian Unified Health System (SUS); Brazilian expertise in public health programs successfully implemented; currently available policies targeting HTLV; and strong collaboration with researchers and patient's representative. Lack of awareness about HTLV, insufficient epidemiological data, lack of reference centers for patient care, insufficient availability of confirmatory tests, lack of universal antenatal screening, and absence of cost-effectiveness studies were identified as weaknesses. Some interesting opportunities included the increased interest from international organizations on HTLV, possibility of integrating HTLV into other programs, external funding for research, available online platforms, opportunity to acquire data from HTLV-1/2 surveillance to gather epidemiological information, and HTLV policies that were implemented independently by states and municipalities. In addition to the COVID-19 pandemic, existing demands from different diseases, the country's demography and its marked sociocultural diversity and the volatility of the technical team working with HTLV-1/2 at the Brazilian Ministry of Health are threats to the implementation of public policies on HTLV-1/2. This SWOT analysis will facilitate strategic planning to allow continuous progress of the Brazilian response to HTLV-1/2 infection.